Analysis of the Effect of Product Quality and Price Discounts on Customer Satisfaction in the Fast Food Industry - Ni Putu Angelina Putri Wirastiwi; Jassincha Khansa Duandri (The Journal of Management, Digital Business, and Entrepreneurship, 2025)
This study aims to analyze the effect of product quality and price discounts on McDonald's customer satisfaction in Bali. The background of this research is based on the phenomenon of declining McDonald's revenue in the first quarter of 2021, which indicates that there are certain factors that affect customer satisfaction. The research method uses a quantitative approach with an associative design, where data is collected through questionnaires to 80 McDonald's customer respondents. The analysis technique used is multiple linear regression to determine the partial and simultaneous effects between the variables studied. This research is expected to contribute to academic literature and become a practical reference in marketing strategy. The results showed that product quality and price discounts have a positive and significant effect on customer satisfaction. The product quality variable has a significance value of 0.039, while the price discount has a significance value of 0.007, both of which are smaller than 0.05. This confirms that the higher the quality of the products offered and the more attractive the price discounts given, the greater the level of customer satisfaction created. However, the coefficient of determination of 18.3% indicates that there are other factors that are more dominant in influencing customer satisfaction. Therefore, companies need to expand the focus of their marketing strategies to be more comprehensive and sustainable.